Weapons of affect: The imperative for transdisciplinary information systems design. Issue 1 (1st February 2019) - Rolan, Gregory; Evans, Joanne; Bone, Jane; Lewis, Antonia; Golding, Frank; Wilson, Jacqueline; McKemmish, Sue; Mendes, Philip; Reeves, Keir
ABSTRACT: Much has been written about ethical and human‐centred Information Systems (IS) design, most recently regarding the deleterious outcomes and negative affect of some machine learning applications that embed and perpetuate unethical or even inhumane automation. Terms such as 'harm', 'damage', and surprisingly, 'weapon' have entered the language of this discourse. However, these characteristics are not unique to applications of data science but have long manifested in IS that can also can exhibit opacity and establish tight vicious cycles. These, when coupled with a lack of governance feedback, can perpetuate injustice that has community or sector‐wide reach. In this paper, we explore how IS design that sets out with the best of intentions or at least, conceived as a 'neutral' system for managing transactional information, can emerge as 'tools that punish'. We argue that there are crucial principles to be taken from Recordkeeping Informatics, concerned as it is with the entanglement of information and people across space and through time on multi‐generational timescales. In particular we discuss how transdisciplinary and critical approaches are necessary to cover more of the design space and surface issues, rights, stakeholders, and, most importantly, values that may be otherwise hidden from a here‐and‐now, transactional viewpoint.